E-Waste Management in Benue State: A Case Study of Mobile Phone Wastes in Makurdi Metropolis (Journal of Environment Sciences, 2025)
Due to the rapid increase in population, rapid urbanization, increased technological advancement which has led to an increase in the use of Electrical and Electronic Equipment (EEE) worldwide, e-waste has become a critical environmental issue for many governments and the world. To address this challenge, this study investigates the management of mobile phone wastes in Makurdi, Benue State. Enquiries were made as to identify the sources, management and identification of those involved in phone waste management. Employing the descriptive research design using qualitative research and quantitative data in its approach through the use of semi-structured interviews conducted using questionnaires based on a sample size selected. The study explored the practices of e-waste disposal and recycling among residents to which a total of four hundred respondents were interviewed in ten (10) out of the eleven (11) council wards in Makurdi LGA. Findings revealed that 55.75% of mobile phones and accessories are sourced in the state, 29.75% from outside the state but within Nigeria and 14.5% came from outside Nigeria. A predominant reliance on informal recycling channels, with most mobile phones sold to scrap dealers (53.5%), primarily based outside the study area was also identified. The absence of formal recycling facilities within Makurdi exacerbates the issue, leading to indiscriminate dumping of phone waste. This research underscores the urgent need for a comprehensive e-waste management system in the region to mitigate environmental and health risks, recover valuable resources, and promote sustainable development.